Tailoring an evidence-based clinical intervention and training package for the treatment and prevention of comorbid heavy drinking and depression in middle-income country settings: the development of the SCALA toolkit in Latin America - Amy O'Donnell; Peter Anderson; Christiane Schmidt; Fleur Braddick; Hugo Lopez-Pelayo; Juliana Mejía-Trujillo; Guillermina Natera; Miriam Arroyo; Natalia Bautista; Marina Piazza; Ines V. Bustamante; Daša Kokole; et al. (Taylor & Francis Group, 2022)
Background Effective interventions exist for heavy drinking and depression but to date there has been limited translation into routine practice in global health systems. This evidence-to-practice gap is particularly evident in low- and middle-income countries. The international SCALA project (Scale-up of Prevention and Management of Alcohol Use Disorders and Comorbid Depression in Latin America) sought to test the impact of multilevel implementation strategies on rates of primary health care-based measurement of alcohol consumption and identification of depression in Colombia, Mexico, and Peru. Objective To describe the process of development and cultural adaptation of the clinical intervention and training package. Methods We drew on Barrero and Castro's four-stage cultural adaption model: 1) information gathering, 2) preliminary adaption, 3) preliminary adaption tests, and 4) adaption refinement. The Tailored Implementation in Chronic Diseases checklist helped us identify potential factors that could affect implementation, with local stakeholder groups established to support the tailoring process, as per the Institute for Healthcare Improvement's Going to Scale Framework. Results In Stage 1, international best practice guidelines for preventing heavy drinking and depression, and intelligence on the local implementation context, were synthesised to provide an outline clinical intervention and training package. In Stage 2, feedback was gathered from local stakeholders and materials refined accordingly. These materials were piloted with local trainers in Stage 3, leading to further refinements including developing additional tools to support delivery in busy primary care settings. Stage 4 comprised further adaptions in response to real-world implementation, a period that coincided with the onset of the COVID-19 pandemic, including translating the intervention and training package for online delivery, and higher priority for depression screening in the clinical pathway. Conclusion Our experience highlights the importance of meaningful engagement with local communities, alongside the need for continuous tailoring and adaptation, and collaborative decision-making.